Mass-Individualisation – the twenty first century manufacturing paradigm. Issue 24 (17th December 2022) - Gu, Xi; Koren, Yoram
Abstract : The forthcoming paradigm of Mass-Individualisation will combine the low-cost advantage of the Mass-Production paradigm with the buyer's individual need of a specific product. The buyers will initiate the product and its features that fit their explicit taste and individual needs, and the manufacturer will build it at low cost in a local factory, which enables a rapid communication of the factory with the buyer. The realisation of the mass-individualisation paradigm requires innovations in (a) product development, (b) manufacturing system and network design, (c) system operations, and (d) business strategies. New factories will have to be in proximity to the customers who participate in the design of their product, which will have an enormous economic impact on local economies. We elaborate on the research challenges and directions for the realisation of the emerging mass-individualisation paradigm.